1997
DOI: 10.1007/s002449900181
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Polychlorinated Naphthalene Congeners in Environmental and Source-Related Samples

Abstract: Polychlorinated naphthalene (CN) congener profiles inenvironmental and source related samples were compared graphically and byprincipal component analysis. Samples investigated included biological,sediment, water, and air samples, technical polychlorinated biphenyl (PCB)and polychlorinated naphthalene (PCN) formulations, as well as municipalwaste incineration (MWI) fly ash and graphite electrode sludge. Biologicalsamples showed a preferential enrichment of planar, 1,3,5,7-substitutedtetra-, penta-, and hexachl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 25 publications
5
76
3
Order By: Relevance
“…Among the individual congeners, PCN73, PCN30/27/39, PCN75, PCN 33/34/37, PCN-66/ 67 and PCN28/43 were the major components in sediments accounting for 15.4%, 13.9%, 13.6%, 6.9%, 6.8% and 6.6%, respectively, of the total PCN concentrations (Fig 4c). Relative higher contributions of PCN73 suggested that the chlor-alkali processes or combustion sources may be the potential sources of PCNs in our study area (Järnberg et al, 1997;Falandysz, 1998;Kannan et al, 1998).…”
Section: Compositions Of Pcdd/fs Pcbs and Pcnsmentioning
confidence: 83%
“…Among the individual congeners, PCN73, PCN30/27/39, PCN75, PCN 33/34/37, PCN-66/ 67 and PCN28/43 were the major components in sediments accounting for 15.4%, 13.9%, 13.6%, 6.9%, 6.8% and 6.6%, respectively, of the total PCN concentrations (Fig 4c). Relative higher contributions of PCN73 suggested that the chlor-alkali processes or combustion sources may be the potential sources of PCNs in our study area (Järnberg et al, 1997;Falandysz, 1998;Kannan et al, 1998).…”
Section: Compositions Of Pcdd/fs Pcbs and Pcnsmentioning
confidence: 83%
“…This is in agreement with the ratios in fly ash from a municipal waste incinerator [16] , but quite different with that in Halowax mixtures, which is dominated by CN-1. CN-44, 39, 51, 54 and 70 are detected in sludge samples with low concentrations, while these congeners were not present in Halowax mixtures, therefore, they are considered as combustion-related indictor congeners [16,21] . Moreover, Järnberg et al [21] found an increase in CN-52/60, 66/67 and 73 in fly ash and a chloralkali sample compared to the Halowax 1014.…”
Section: Pcn Congener Patterns and Possible Sourcesmentioning
confidence: 99%
“…CN-44, 39, 51, 54 and 70 are detected in sludge samples with low concentrations, while these congeners were not present in Halowax mixtures, therefore, they are considered as combustion-related indictor congeners [16,21] . Moreover, Järnberg et al [21] found an increase in CN-52/60, 66/67 and 73 in fly ash and a chloralkali sample compared to the Halowax 1014. Furthermore, in the present study, the ratio of CN-73/CN-74 in HpCNs with the range of 1.8-3.1 is close to that described by Järnberg et al [22] and Gevao et al [23] for contaminations from combustion sources, but much higher than CN-73/CN-74 ratios with the range of 0.2-0.4 in Halowax mixtures [24] .…”
Section: Pcn Congener Patterns and Possible Sourcesmentioning
confidence: 99%
“…3), indicating that re-emission of technical CN/CB formulations might be the main sources. PCNs from household combustion such as coal and wood combustion (Wyrzykowska et al, 2009), PCNs as byproducts from chloralkali plants (Järnberg et al, 1997;Kannan et al, 1998) and PCNs existing as impurities in other industrial products (Pan et al, 2011) might also be possible contributors for the low ratios, although these sources are currently difficult to identify due to insufficient information.…”
Section: Possible Sourcesmentioning
confidence: 99%